Organizational culture in general hospitals and its relationship with job satisfaction - Katja Skinder Savić; Brigita Skela-Savič (Nurses and Midwives Association of Slovenia, 2014)
Introduction: Organizational culture is formed via communication, resolving conflicts, team work and interconnection. The aim of the study was to present the connections between organizational culture and job satisfaction indicators. Methods: A quantitative descriptive approach was used. The study included nursing employees and medical practitioners in six Slovenian hospitals. A 30 per cent quota sample was used, with a response rate of 35.2 % (n = 310). The Organization Culture Assessment Instrument (OCAI) (α = 0,818) and Index of Work Satisfaction (α = 0,921) questionnaires were used. The data was processed with SPSS 20.0 statistical software by using the t-test, single variance analysis, correlation, factor and regression analysis. Results: The greatest total average value among employees of both job groups with regard to organizational culture was the market (x = 28.21) and hierarchy (x = 27.57). Job satisfaction indicators (collaboration, leadership, decision-making, autonomy) can be explained in 20 % of cases with adhocracy organizational culture (β = 0.318, p < 0.001), market (β = 0.219, p < 0.001) and clan (β = 0.161, p = 0.006). Discussion and conclusion: In Slovenian hospitals, control over work, abiding by the rules and attaining, goals prevails. An overview of the literature reveals the influence of culture on satisfaction. Other factors affecting satisfaction, including stress and abuse of hierarchical power, should be studied.